The epidemiology of sepsis in paediatric intensive care units in Brazil (the Sepsis PREvalence Assessment Database in Pediatric population, SPREAD PED): an observational study. (December 2021) - de Souza, Daniela Carla; Gonçalves Martin, Joelma; Soares Lanziotti, Vanessa; de Oliveira, Cláudio Flauzino; Tonial, Cristian; de Carvalho, Werther Brunow; Roberto Fioretto, José; Pedro Piva, Jefferson; Juan Troster, Eduardo; Siqueira Bossa, Aline; Gregorini, Flávia; Ferreira, Josiane; et al.
Summary: Background: Data on the prevalence and mortality of paediatric sepsis in resource-poor settings are scarce. We aimed to assess the prevalence and in-hospital mortality of severe sepsis and septic shock treated in paediatric intensive care units (PICUs) in Brazil, and risk factors for mortality. Methods: We performed a nationwide, 1-day, prospective point prevalence study with follow-up of patients with severe sepsis and septic shock, using a stratified random sample of all PICUs in Brazil. Patients were enrolled at each participating PICU on a single day between March 25 and 29, 2019. All patients occupying a bed at the PICU on the study day (either admitted previously or on that day) were included if they were aged 28 days to 18 years and met the criteria for severe sepsis or septic shock at any time during hospitalisation. Patients were followed up until hospital discharge or death, censored at 60 days. Risk factors for mortality were assessed using a Poisson regression model. We used prevalence to generate national estimates. Findings: Of 241 PICUs invited to participate, 144 PICUs (capacity of 1242 beds) included patients in the study. On the day of the study, 1122 children were admitted to the participating PICUs, of whom 280 met the criteria for severe sepsis or septic shock during hospitalisation, resulting in a prevalence of 25·0% (95% CI 21·6–28·8), with a mortality rate of 19·8% (15·4–25·2; 50 of 252 patients with complete clinical data). Increased risk of mortality was associated with higher Pediatric Sequential Organ Failure Assessment score (relative risk per point increase 1·21, 95% CI 1·14–1·29, p<0·0001), unknown vaccination status (2·57, 1·26–5·24; p=0·011), incomplete vaccination status (2·16, 1·19–3·92; p=0·012), health care-associated infection (2·12, 1·23–3·64, p=0·0073), and compliance with antibiotics (2·38, 1·46–3·86, p=0·0007). The estimated incidence of PICU-treated sepsis was 74·6 cases per 100 000 paediatric population (95% CI 61·5–90·5), which translates to 42 374 cases per year (34 940–51 443) in Brazil, with an estimated mortality of 8305 (6848–10 083). Interpretation: In this representative sample of PICUs in a middle-income country, the prevalences of severe sepsis or septic shock and in-hospital mortality were high. Modifiable factors, such as incomplete vaccination and health care-associated infections, were associated with greater risk of in-hospital mortality. Funding: Fundação de Amparo à Pesquisa do Estado de São Paulo and Conselho Nacional de Desenvolvimento Científico e Tecnológico. Translation: For the Portuguese translation of the abstract see Supplementary Materials section.